Temporary Auricular Prosthesis Acrylic Resin With Eyeglasses Retention To Improve Aestetics In Patient With Ear Loss Case (Case Report ) - Endang Prawesthi; Dita Syafitri (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2019)
Total ear defects in the form of losing the entire outer ear or only part of the ear will definitely affect for patient's confidence. Defect or loss of the ear can be caused by birth defects, acquired diseases or accidents. So, it takes a prosthese that functions to replace the lossing ear part, namely auricular prosthesis, so that the patient will feel confident again with his appearance. Temporary prosthesis is an alternative method that can be used in the short term before the use of a permanent prosthesis (definitive prosthesis). The purpose of this paper is to find out how to make temporary auricular prosthesis acrylic resin with retention eyeglasses to improve aestetics in patient with ear loss case. The method used is a case study (model) which is conventionally made, with moulding using donor techniques. In making temporary auricular prosthesis consists of several stages starting from the acceptance of the work model, the making of the wax pattern, flasking, boiling out, coloring, packing, curing, deflasking, finishing, polishing and sticking of retention. The results obtained are temporary auricular prosthesis can sticking well with eyeglasses stalks, there is no porous, the color does not match the work order and the polishing results are less smooth but quite shiny. The conclusion is that temporary auricular prosthesis in cases of repair of ear defects can be made using acrylic resin with mechanical retention of eyeglasses.